2014
DOI: 10.1159/000363205
|View full text |Cite
|
Sign up to set email alerts
|

Role of Riboflavin- and UV Light-Treated Plasma in Prevention of Transfusion-Related Acute Lung Injury

Abstract: Introduction: Risk reduction strategies for transfusion-related acute lung injury (TRALI) include the preferential use of male donors to provide fresh frozen plasma (FFP). Implementing this measure based on FFP quarantine program is a very complex process. To improve FFP inventory management and the availability of FFP from male donors, the Mirasol Pathogen Reduction Technology® (PRT) system for FFP using riboflavin and UV light was adopted in our region in 2012. Methods: The percentage of male/female FFP unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…In total, 48 studies reported rates for five types of transfusion reactions, providing a total of 120 separately reported transfusion reaction rates—allergic transfusion reactions (35), FNHTRs (18), transfusion‐associated circulatory overload (TACO) (9), anaphylactic transfusion reactions (12), and transfusion‐related acute lung injury (TRALI) (46). The 48 studies, many of which reported on transfusion reaction rates for multiple plasma types, investigated AI‐FFP (4), SDP (8), MO‐FFP (7), MB‐FFP (3), and MS‐FFP (39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 48 studies reported rates for five types of transfusion reactions, providing a total of 120 separately reported transfusion reaction rates—allergic transfusion reactions (35), FNHTRs (18), transfusion‐associated circulatory overload (TACO) (9), anaphylactic transfusion reactions (12), and transfusion‐related acute lung injury (TRALI) (46). The 48 studies, many of which reported on transfusion reaction rates for multiple plasma types, investigated AI‐FFP (4), SDP (8), MO‐FFP (7), MB‐FFP (3), and MS‐FFP (39).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were performed between 2001 and 2016 in 20 different countries and included observations from over 25 million transfusions. Complete study characteristics and extracted data, along with their ROBINS‐I evaluations, are provided in Table S1 (available as supporting information in the online version of this paper) …”
Section: Resultsmentioning
confidence: 99%
“…In 2012, the Balearic Islands Blood Bank (BIBB) implemented riboflavin and UV light PRT for plasma (Mirasol PRT, Terumo BCT Europe N.V.). 18 In 2013, the BIBB initiated universal routine use of riboflavin and UV light-treated PLTs for transfusion support in patients with thrombocytopenia. In this blood center, we have recently experimentally studied the effectiveness of riboflavin and UV light in eliminating T. cruzi from WB units.…”
Section: Study Design and Methods: A Retrospectivementioning
confidence: 99%
“…In 2014 several papers considered the influence of blood product characteristics or modifications on product safety and transfusion efficacy [2][3][4][5][6]. The current issue deals with the nationwide implementation of pathogen inactivation (PI) for all platelet concentrates (PC) in Switzerland, as presented by Markus Jutzi and colleagues [7].…”
mentioning
confidence: 99%